Feeding Practices and Early Childhood Caries: A Cross-Sectional Study of Preschool Children in Kanpur District, India - Prakasha Shrutha, Santhebachalli (Hindawi Publishing Corporation, 2013)
Background. Early childhood caries (ECC) is a public health problem due to its impact on children's health, development, and wellbeing. The objective of this study was to assess the caries experience in 3–5-year-old children and to evaluate the relationship with their mothers' practices regarding feeding and oral hygiene habits in Kanpur. Method. A cross-sectional survey was undertaken on 2000 (974 boys and 1026 girls) children aged 3–5 years from a random sample of preschools in Kanpur district, India. Dental caries experience was recorded using WHO criteria. A pretested questionnaire with 9 questions was used for collecting information regarding mothers' practices regarding feeding and oral hygiene practices. Chi-square test (χ (2)) and Student's t-test were used for statistical analysis. Results. The prevalence of ECC was 48% with mean dmft of 2.03 ± 2.99. Boys (57%) were affected more than girls (43%) which was found to be statistically significant (P < 0.05). Caries prevalence was high and statistically significant (P < 0.05) among those who were breast fed for longer duration, during nighttime, those falling asleep with bottle, and those fed with additional sugar in milk. Conclusion. Determining the role of feeding practices on early childhood caries can help in the development of appropriate oral health promotion strategies.